NATURE BASED LIVING LAB - Quishpe, Luis-Miguel; CEDIA (2024)
Rainforests play a practical role in keeping our planet healthy by absorbing carbon dioxide and releasing the oxygen that humans depend on for survival. Absorption of carbon dioxide also helps to stabilize the climate of Earth. In addition, rainforests help to maintain the world water cycle by adding water to the atmosphere through the process of transpiration, which creates clouds. Get wild about saving the Amazonian Rainforest! Our initiative creates space for young researchers from all over the world who want to contribute to its protection. NB-LAB = Nature-based living lab for interdisciplinary practical and research semester on sustainable development and environmental protection in the Amazonas Rainforest.